The female character as reader in Alice Munro’s stories: “at the end of it all what has been accomplished?” - Christine LORRE (E-REA)
This article studies the female character as reader in a selection of Alice Munro’s short stories, focusing on how these characters are re-examined, over time, so that the reader perceives them differently, in the same way as the characters themselves perceive a change in their own development. The aim is to examine how reading persistently plays a role in different forms of character development, which expresses itself through identification, rejection, or doubt, whether in a community, an age group, a social class, or in a couple.